2002
DOI: 10.1096/fj.01-0866com
|View full text |Cite
|
Sign up to set email alerts
|

Activation of an alternative NF‐ΚB pathway in skeletal muscle during disuse atrophy

Abstract: Although cytokine-induced nuclear factor kappaB (NF-kappaB) pathways are involved in muscle wasting subsequent to disease, their potential role in disuse muscle atrophy has not been characterized. Seven days of hind limb unloading led to a 10-fold activation of an NF-kappaB-dependent reporter in rat soleus muscle but not the atrophy-resistant extensor digitorum longus muscle. Nuclear levels of p50 were markedly up-regulated, c-Rel was moderately up-regulated, Rel B was down-regulated, and p52 and p65 were unch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
239
6
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(271 citation statements)
references
References 68 publications
22
239
6
4
Order By: Relevance
“…Data from our lab [17,19] and others [45] have consistently shown an increase in the protein content for Bcl-2 following disuse and in aged muscles, with further increases when disuse is superimposed with aging. This led to our hypothesis that aged muscles attempt to counteract pro-apoptotic stimuli by up-regulating anti-apoptotic proteins.…”
Section: Apoptotic Changes In Aged Skeletal Musclesupporting
confidence: 55%
“…Data from our lab [17,19] and others [45] have consistently shown an increase in the protein content for Bcl-2 following disuse and in aged muscles, with further increases when disuse is superimposed with aging. This led to our hypothesis that aged muscles attempt to counteract pro-apoptotic stimuli by up-regulating anti-apoptotic proteins.…”
Section: Apoptotic Changes In Aged Skeletal Musclesupporting
confidence: 55%
“…There are few studies which have looked at NF-kB activation in skeletal muscle under conditions of muscle wasting. However, a recent study (Hunter et al, 2002) showed nuclear extracts from the soleus muscle of rats undergoing disuse atrophy to show increased binding of NF-kB oligonucleotides. This complex bound antibody to p50, c-Rel and Bcl-3, but not other NF-kB members, and there was no evidence for the canonical NFkB pathway involving activation of p65 or I-kBa.…”
Section: Discussionmentioning
confidence: 97%
“…Nuclear factor-kB may also be involved in other conditions of muscle wasting. Thus, hind-limb unloading, a model of disuse atrophy, resulted in a 10-fold increase in the activity of a transfected NF-kB-dependent reporter (Hunter et al, 2002), but this involved p50, c-Rel and Bcl-3 and not activation of p65 or I-kB, and is thus distinct from cachexia. This suggests that inhibitors of the release and subsequent nuclear translocation of NF-kB, or the binding of NF-kB to DNA should be evaluated as potential agents to prevent muscle atrophy in cancer cachexia.…”
Section: Discussionmentioning
confidence: 97%